2020
DOI: 10.1101/2020.07.15.20154336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological Profile and Transmission Dynamics of COVID-19 in the Philippines

Abstract: The Philippines confirmed local transmission of COVID-19 on 7 March 2020. We described the characteristics and epidemiological time-to-event distributions for laboratory-confirmed cases in the Philippines. The median age of 8,212 cases was 46 years (IQR: 32-61), with 46.2% being female and 68.8% living in the National Capital Region. Health care workers represented 24.7% of all detected infections. Mean length of hospitalization for those who were discharged or died were 16.00 days (95% CI: 15.48, 16.54) and 7… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
4
13
0
1
Order By: Relevance
“…13 Patients in this study are also mainly from the older age range, with the 51-60 and 61-70 having the most number combined; this may be because PGH is a COVID-19 referral center generally receiving patients that are critically ill and needing tertiary care which in all likelihood will be those who are older. More than half of those admitted are male (55.72%), similar to the reported sex predominance in other local epidemiological studies 14,15 and the weekly WHO COVID-19 Philippine situational report since April 2020. 16 Vulnerable individuals were identified as minors, elderly above 60 years of age, pregnant women, and those having considerable underlying health conditions.…”
Section: Discussionsupporting
confidence: 87%
“…13 Patients in this study are also mainly from the older age range, with the 51-60 and 61-70 having the most number combined; this may be because PGH is a COVID-19 referral center generally receiving patients that are critically ill and needing tertiary care which in all likelihood will be those who are older. More than half of those admitted are male (55.72%), similar to the reported sex predominance in other local epidemiological studies 14,15 and the weekly WHO COVID-19 Philippine situational report since April 2020. 16 Vulnerable individuals were identified as minors, elderly above 60 years of age, pregnant women, and those having considerable underlying health conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The seroprevalence of SARS-CoV-2 found in Sergipe state was distributed heterogeneously according to geographical location, with higher prevalence in metropolitan area than other municipalities. This supports the findings of previous studies which showed higher rates of SARS-CoV-2 infection in populations living in highly dense areas compared to areas with a smaller population [3,10,14,15].…”
Section: Discussionsupporting
confidence: 91%
“…While we included “adjuster” parameters to allow the symptomatic proportion, hospitalisation, and mortality rates to vary for the Philippines (similar to 25), we assumed that other parameters were similar to HIC, which may be inaccurate. However, most parameter estimates appear reasonable given previously reported COVID-19 epidemiology in the Philippines (26). When more data becomes available from the Philippines or similar settings, the current model can be updated with new parameter values.…”
Section: Discussionsupporting
confidence: 77%